2022
DOI: 10.14745/ccdr.v48i23a05
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of two point-of-care test kits for the identification of infectious syphilis

Abstract: Background: Syphilis is a sexually transmitted disease that can have atypical clinical presentations. Conventional laboratory tests to confirm the diagnosis are not rapid enough to affect clinical decision on treatment and contact tracing. Rapid point-of-care tests (POCT) can be useful for control of infectious diseases; however, no POCT for syphilis detection is currently available in Canada. The aim of this study is to evaluate two POCTs (RevealTM Rapid TP (Treponema pallidum) Antibody test and DPP® Syphilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A further innovative practice would be to incorporate a syphilis point-of-care test in conjunction with outreach services, allowing persons to be diagnosed and treated at the same visit, while reducing barriers to accessing care. Recent trials of one such test have shown good sensitivity for cases with RPR ≥8 dilutions, which would have included all our cases 16,17 . One must also keep in mind the motto “Treatment is prevention.” Improved diagnosis and treatment of syphilis before pregnancy and of sexual partners will decrease the incidence of syphilis in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A further innovative practice would be to incorporate a syphilis point-of-care test in conjunction with outreach services, allowing persons to be diagnosed and treated at the same visit, while reducing barriers to accessing care. Recent trials of one such test have shown good sensitivity for cases with RPR ≥8 dilutions, which would have included all our cases 16,17 . One must also keep in mind the motto “Treatment is prevention.” Improved diagnosis and treatment of syphilis before pregnancy and of sexual partners will decrease the incidence of syphilis in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The RVF Core Technology test has been reported before [ 36 , 37 , 38 , 39 ]. The ACT::SOE3 recombinant protein at a concentration of 1 mg/mL is formulated in PBS, pH 7.5, containing 0.1% Tweet 20, 0.6% SDS, 10 mM EDTA and 0.01% of sodium azide.…”
Section: Methodsmentioning
confidence: 99%
“…The RDT that will be used in this study is the Chembio DPP 1 Syphilis Screen & Confirm Assay (Chembio Diagnostic Systems Inc., Medford, NY; Chembio RDT) [13]. Previously published evaluations of the diagnostic accuracy of the Chembio RDT indicate that when using serum, the RDT has acceptable sensitivity (�85%) and specificity (�94%) relative to traditional laboratory-based diagnostic approaches [14][15][16][17][18]. The majority of these studies however, have been conducted either in laboratory settings or by trained laboratory personnel which may bias the observed accuracy.…”
Section: Study Aimsmentioning
confidence: 99%